The Influence of Sharia Screening (Business Sector, Leverage, and Financial Ratios) on Investment Decisions - Wilfi Tizka Sari; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
In the context of the Islamic capital market, investment decisions must take into account compliance with Sharia principles, such as the prohibition of riba (interest), gharar (excessive uncertainty), and maysir (gambling), as well as the requirement to invest in halal sectors. These principles are implemented through a Sharia screening mechanism that involves an assessment of the business sector, leverage ratio, and the company’s financial ratios. This study aims to analyze the influence of these three aspects of Sharia screening on corporate investment decisions. Using a descriptive qualitative approach and library research method, data were collected from various secondary sources such as academic journals, DSN-MUI fatwas, and publications from OJK and IDX.The analysis was conducted descriptively to understand the relationship between the Sharia screening aspects and the investment preferences of Sharia-compliant investors.The results indicate that the business sector is the dominant factor in the consideration of Sharia investors, followed by leverage and financial ratios. Therefore, a deep understanding of the Sharia screening mechanism is essentialnot only for investors but also for issuers and regulators in fostering the development of an inclusive capital market based on Islamic principles